2006
DOI: 10.1089/ees.2006.23.908
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Sustainable Urban Drainage System Management Project: Case Studies (Belvidere Hospital and Celtic FC Stadium Areas)

Abstract: The Glasgow Sustainable Urban Drainage System (SUDS) Management Project satisfies the first phase of the Glasgow Surface Water Management Project. This is Glasgow City Council's contribution to the Transformation of Rural and Urban Spatial Structure (TRUST) project, one of the European Union's (EU) interregional (INTERREG IIIB) funded research projects. The remit of this EU project comprises also other representative regions in Europe. The project shows also how SUDS can contribute to the overall catchment dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The relatively high variability for most variables such as ponds and constructed wetlands cannot be explained by factors relating to specific planning policies for Greater Manchester. Ponds are associated with the greatest inter-site variability because of their potentially relatively small size and great popularity [5,6,19]. Note: * Proportion (%) of sites at which sustainable drainage system techniques are given first, second or third order of preference based on different professional perspectives (weights in Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relatively high variability for most variables such as ponds and constructed wetlands cannot be explained by factors relating to specific planning policies for Greater Manchester. Ponds are associated with the greatest inter-site variability because of their potentially relatively small size and great popularity [5,6,19]. Note: * Proportion (%) of sites at which sustainable drainage system techniques are given first, second or third order of preference based on different professional perspectives (weights in Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The standard site assessment template was based on a combination of the frameworks developed by Scholz and his team for retrofitting of SuDS techniques in Glasgow, Edinburgh and elsewhere [4,6], and the Construction Industry Research and Information Association guidelines [1,13]. Each potential SuDS site was assessed during a site visit by a group of experts (2 to 5 team members) to reduce subjectivity [14].…”
Section: Site Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…and receiving water ecology and habitat (Scholtz 2005 ). In a parallel study elsewhere in Glasgow, Scholtz et al (2006) suggested the use of below -ground storage in combination with surface swales and attenuation ponds as an alternative drainage solution which would reduce the pressure on land take. As much as 110,000 m 2 might be taken out of the Gadburn development site for the construction of SUDS, which would represent a substantial capital loss to the developers.…”
Section: Support S Ystemsmentioning
confidence: 99%
“…The proposed classification methodology follows a similar rationale as the novel classification key for ditches in wetlands Table 9 Prioritisation example for classification variables (see Table 1 (Scholz, 2006;Scholz and Lee, 2005;Scholz and Trepel, 2004) and the Sustainable Urban Drainage Decision Support Model (Scholz, 2006;Scholz et al, 2006). However, the selected classification variables are obviously different.…”
Section: Classification Systems and Variables And Their Wider Contextmentioning
confidence: 99%